2013
DOI: 10.1016/j.cardfail.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Consultations for Heart Failure Patients: How Many, When, and Why?

Abstract: Background-In preparation for development of a palliative care intervention for patients with heart failure (HF) and their caregivers, we aimed to characterize the HF population receiving palliative care consultations (PCCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 56 publications
3
81
0
3
Order By: Relevance
“…31,32,[36][37][38] The negative effects of ethical conflicts are widespread for patients, patients' families, and health care providers. Quality care and patient safety are threatened when health care providers are burdened by stressful ethical conflicts that erode interpersonal trust, compromise working relationships, and fragment care.…”
Section: Study Procedures and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32,[36][37][38] The negative effects of ethical conflicts are widespread for patients, patients' families, and health care providers. Quality care and patient safety are threatened when health care providers are burdened by stressful ethical conflicts that erode interpersonal trust, compromise working relationships, and fragment care.…”
Section: Study Procedures and Data Collectionmentioning
confidence: 99%
“…Similarly, Morden et al 31 reported that Medicare recipients with cancer received aggressive treatments, such as ventilator support, relative to their poor prognosis in the last weeks of life. Bakitas et al 32 also reported that heart failure patients are not often referred for palliative care services until the last month of life and suggested that advance care planning is often delayed.…”
Section: Introductionmentioning
confidence: 99%
“…13,27,87,102,[106][107][108] However, patients and caregivers with heart failure access palliative services far less often than patients with cancer. 105,109 Even in cases when patients with heart failure are referred for palliative care, consultations are initiated only very late in the care trajectory. 109 Although not synonymous, end-of-life care and palliative care overlap in many ways.…”
Section: May 8 2018mentioning
confidence: 99%
“…105,109 Even in cases when patients with heart failure are referred for palliative care, consultations are initiated only very late in the care trajectory. 109 Although not synonymous, end-of-life care and palliative care overlap in many ways. A recent study of older adults' caregivers at the end of life examined 900 000 community-dwelling Medicare beneficiaries who received support from 2.3 million caregivers.…”
Section: May 8 2018mentioning
confidence: 99%
“…Other studies report various unmet palliative care needs in patients with advanced heart failure [6,7]. Although some studies suggest beneficial effects of palliative care consultation [8][9][10][11][12], less than 10% of patients with heart failure receive palliative care today [13,14].…”
Section: Introductionmentioning
confidence: 99%